Hubungan Pola Asuh Orang Tua Dengan Kemandirian Anak Usia Prasekolah Di Desa Bangun Rejo Kecamatan Kecamatan Tanjung Morawa Tahun 2024 - Indra Agussamad; Lisdayanti Simanjuntak; Martaulina Sinaga; Adelina Sembiring4; Vinsen Kripeni Manik; Yessy Winata Hutagalung (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
Children are small humans who have potential that must be developed. Children have certain characteristics that are unique and not the same as adults, they are always active, dynamic and curious about what they see, hear, feel and they never seem to stop exploring and learning. Children are egocentric, and have a natural curiosity. Research Objectives: To determine the relationship between parenting patterns and the independence of preschool-age children in Bangun Rejo Village, Tanjung Morawa District. This research design uses a correlation study. The sample in this study used a total sampling technique. From the results of univariate data analysis, it can be seen that authoritarian parenting patterns for preschool age children are in the non-authoritarian category, namely 26 respondents (26.8%). Democratic parenting styles for children are in the non-democratic category, namely 22 respondents (53.7%). The majority of permissive parenting styles for children are in the permissive category, namely 21 people (51.2%). The independence of preschool age children is mostly in the independent category, namely 22 (46.3%). The results of the bivariate data analysis. The statistical test results show that the p-value is 0.536 ˃ 0.05 so that the null hypothesis (Ho) is accepted, which means there is no significant relationship between authoritarian parenting and the independence of preschool-age children, and the statistical test results show that the p-value -value 0.257 ˃ 0.05 so the null hypothesis (Ho) is accepted which means there is no significant relationship between democratic parenting and the independence of preschool aged children. Then the results of statistical tests show that the p-value is 0.278 ˃ 0.05 so the null hypothesis ( Ho) is accepted, which means there is no significant relationship between parenting styles and the independence of preschool-aged children.